Biophysical Analysis of the Land Carrying Capacity to Organic Rice Plantations in Jember, East Java, Indonesia - Hoesain, Mohammad; Pradana, Ankardiansyah Pandu; Alfarisy, Fariz Kustiawan; Soekarno, Siswoyo; Wahyuningsih, Sri; Al Ramadhani, Farchan Mushaf (AGRIVITA Journal of Agricultural Science, 2025)
Organic rice is cultivated without synthetic materials, offering high economic value and health benefits. Supportive biophysical components are essential for optimal growth and improving organic rice productivity. This research aims to identify the biophysical components that contribute to the land's carrying capacity for organic rice growth. The research was conducted in Rowosari Village, Jember Regency, East Java. The study analyzed on-farm activities, including producing organic fertilizers and pesticides, land mapping, agroclimate, and assessing biological components. The results show that biophysical factors significantly influence organic rice growth. Indicators of the success of organic fertilizer produced are N of 0.15%, P of 0.04%, K of 0.22%, and fertilizer pH of 4.98. The qualitative analysis of organic pesticides revealed the presence of secondary metabolites like tannin, saponin, flavonoid, alkaloid, and terpenoid with the code (+++). A high biological diversity was observed, with a Shannon-H index exceeding 1. Additionally, the concentration of organic fertilizers and pesticides significantly increased the number of rice plant saplings during the vegetative phase. The study concludes that the biophysical components of the land provide strong support for the growth of organic rice, demonstrating their vital role in the sustainability and productivity of organic farming systems.